2010
DOI: 10.1158/0008-5472.sabcs10-s4-2
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S4-2: First Efficacy Results of a Randomized, Open-Label, Phase III Study of Adjuvant Doxorubicin Plus Cyclophosphamide, Followed by Docetaxel with or without Capecitabine, in High-Risk Early Breast Cancer

Abstract: Background: Combination regimens incorporating anthracyclines and taxanes are among the most effective for EBC and are particularly suitable for pts with high-risk disease. Significant efficacy benefit has been shown in phase III trials integrating capecitabine (X) into anthracycline/taxane-containing (neo)adjuvant regimens (Joensuu H, et al. Lancet Oncol 2009; Steger G, et al. ASCO 2010). We present first efficacy results of a large, randomized, multicenter phase III study comparing adjuvant doxorubicin plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…Thus, it appears unlikely that these drugs would add much benefit in the adjuvant setting. Indeed, our results confirm (and would have predicted) the largely negative results of several trials of adjuvant therapy with these drugs, [21][22][23] supporting our hypothesis that trials of neoadjuvant therapy serve as better predictors of adjuvant benefits than studies of metastatic disease. The addition of bevacizumab resulted in a modest but significant increase in the rate of pathological complete response in the breast, but the rate of pathological complete response in the breast and nodes was not significantly increased, which may indicate that this drug will have a lesser effect on patient outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, it appears unlikely that these drugs would add much benefit in the adjuvant setting. Indeed, our results confirm (and would have predicted) the largely negative results of several trials of adjuvant therapy with these drugs, [21][22][23] supporting our hypothesis that trials of neoadjuvant therapy serve as better predictors of adjuvant benefits than studies of metastatic disease. The addition of bevacizumab resulted in a modest but significant increase in the rate of pathological complete response in the breast, but the rate of pathological complete response in the breast and nodes was not significantly increased, which may indicate that this drug will have a lesser effect on patient outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, grade 3/4 infection and neutropenia were seen in the control arm, especially in relation to docetaxel since dose of docetaxel was higher in the control arm [Joensuu et al 2007]. In a similar study, O'Shaughnessy reported a trend for benefit with the addition of capecitabine to docetaxel after adjuvant AC in TNBC patients (HR = 0.64; 95% CI 0.44-0.95) [O'Shaughnessy et al 2010].…”
Section: Treatmentmentioning
confidence: 99%
“…OS erkennen. Diese Verbesserung war jedoch mit einer erhöhten Toxizität verbunden [14,22]. Nach fünf Jahren war die Verbesserung von DFS und OS nicht mehr im Gesamtkollektiv der FinXX-Studie signifikant, sondern nur …”
Section: Substanzenunclassified